2008
DOI: 10.1111/j.1750-3841.2007.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision‐Based Evaluation of Pre‐ and Postrigor Changes in Size and Shape of Atlantic Cod (Gadus morhua) and Atlantic Salmon (Salmo salar) Fillets during Rigor Mortis and Ice Storage: Effects of Perimortem Handling Stress

Abstract: The present study describes the possibilities for using computer vision-based methods for the detection and monitoring of transient 2D and 3D changes in the geometry of a given product. The rigor contractions of unstressed and stressed fillets of Atlantic salmon (Salmo salar) and Atlantic cod (Gadus morhua) were used as a model system. Gradual changes in fillet shape and size (area, length, width, and roundness) were recorded for 7 and 3 d, respectively. Also, changes in fillet area and height (cross-section p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 32 publications
(53 reference statements)
6
41
2
1
Order By: Relevance
“…Low pH at the time of killing is widely recognised as an indicator of handling stress, as reported in salmon [27], eel [28] and turbot [29]. Typical initial muscle pH values reported for exhausted cod is about 7.0 [30][31][32], which is lower than that reported for our cod, namely, pH 7.2-7.3 (Table 5). Surprisingly, this means that the cod in our experiment were just partially affected by capture stress.…”
Section: Discussioncontrasting
confidence: 75%
“…Low pH at the time of killing is widely recognised as an indicator of handling stress, as reported in salmon [27], eel [28] and turbot [29]. Typical initial muscle pH values reported for exhausted cod is about 7.0 [30][31][32], which is lower than that reported for our cod, namely, pH 7.2-7.3 (Table 5). Surprisingly, this means that the cod in our experiment were just partially affected by capture stress.…”
Section: Discussioncontrasting
confidence: 75%
“…Kristoffersen et al [5] reported a higher pH value, 7.9, for farmed cod killed with as little pre-slaughter activity as possible. In our stressed fish, the values were typical, pH 7.0, and were in accordance to previously reported pH values for stressed cod [4][5][6]. Low pH at the time of killing is widely recognised as an indicator of handling stress.…”
Section: Post-slaughter Classification Of Fish According To Stress Levelsupporting
confidence: 74%
“…Comparable values (pH 7.2-7.5) are reported for unstressed farmed Atlantic cod [4,6]. Kristoffersen et al [5] reported a higher pH value, 7.9, for farmed cod killed with as little pre-slaughter activity as possible.…”
Section: Post-slaughter Classification Of Fish According To Stress Levelmentioning
confidence: 71%
See 1 more Smart Citation
“…), and grey mullet (Mugil cephalus) have been successfully separated using images of fish swimming in an aquarium [16]. Besides sorting of fish, CVS has been used to describe the rigor contractions of unstressed and stressed Atlantic salmon (S. salar) and Atlantic cod (G. morhua) fillets by monitoring the transient two-and three-dimensional changes in the geometry [17]. This method has been found suitable for industrial purposes.…”
Section: Visual Quality Determination Based On Size and Shapementioning
confidence: 99%